A feminist reading of an oriental tale: "Crystal manor and diamond ship" - Çetin, Derya; Deveci, Mevlüde (IGI Global, 2022)
Tales, which have an important place in the process of socialization, contain various ideological constructions like other narratives. This study aims to analyses an important tale of Turkey's tale corpus named "Crystal Manor and Diamond Ship" by the terms of feminist critics. This tale is considered among the tales of Anatolian field and is similar to some western tales such as Rapunzel. However, in terms of subject positions, which are one of the focal points of feminist criticism, the main female character, unlike most fairy tales, seems to be planning and implementing the actions that advance the plot, rather than waiting for a man to rescue her. © 2022, IGI Global.